1914
DOI: 10.1002/cber.191404701154
|View full text |Cite
|
Sign up to set email alerts
|

Über das Hexanitro‐äthan

Abstract: Bei der R e d u k t i o n mit Zinkstaub in heiBer Eisessig-Liisung erhirlt man das L a u k o d e r i v a t , das sehr leicht wieder oxydierbar ist. Es schmilzt nach dem Umkrystallisieren a u Eisessig bei 1750, lost sich in den iiblichen Mitteln und in konzentrierter Schwelelsirnre mit schwach graner Farbe (geringe Oxyclation 7). C,sH1602. Ber. C 85.1, H 5.0. Gef. 85.2, B 5.1. Der Methyiiither l a t aich ehenlalls leicht darstellen, wenn man das Produkt in reinem Dimethylsulfat 16st und mit Alkali behandelt. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
2

Year Published

1921
1921
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…Early studies of α‐halogen derivatives of trinitromethane have demonstrated the pseudohalogenic nature of the trinitromethyl moiety 1. Further experimental evidence supporting this behavior as a pseudohalogen are the discoveries of the corresponding strong acid HC(NO 2 ) 3 ,2 various metal salts like K[C(NO 2 ) 3 ] and Ag[C(NO 2 ) 3 ],2b pseudointerhalogen compounds such as NCC(NO 2 ) 3 3 and N 3 C(NO 2 ) 3 ,4 as well as its dimer hexanitroethane 5. Furthermore, the existence of the halogenotrinitromethanes HalC(NO 2 ) 3 (Hal=F, Cl, Br, I) confirm this assumption.…”
Section: Introductionmentioning
confidence: 89%
“…Early studies of α‐halogen derivatives of trinitromethane have demonstrated the pseudohalogenic nature of the trinitromethyl moiety 1. Further experimental evidence supporting this behavior as a pseudohalogen are the discoveries of the corresponding strong acid HC(NO 2 ) 3 ,2 various metal salts like K[C(NO 2 ) 3 ] and Ag[C(NO 2 ) 3 ],2b pseudointerhalogen compounds such as NCC(NO 2 ) 3 3 and N 3 C(NO 2 ) 3 ,4 as well as its dimer hexanitroethane 5. Furthermore, the existence of the halogenotrinitromethanes HalC(NO 2 ) 3 (Hal=F, Cl, Br, I) confirm this assumption.…”
Section: Introductionmentioning
confidence: 89%
“…Halogenated trinitromethane compounds (HTC) which are known as explosives and propellants are also of interest from the fundamental viewpoint. [1][2][3] Indeed, the specific structural organization of these compounds with an electronegative halogen and three nitro groups linked by a common carbon atom [4][5][6] leads to non-trivial mutual atomic influence. Unfortunately, the current interpretation of non-covalent intramolecular interactions in these systems may not seem satisfactory now.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mutual interactions between atoms and functional groups is crucial for the control of chemical reactions and structural properties.T he study of simple yet extreme examples is therefore af undamental challenge,i n particular if the behavior of such systems deviates from the expected one.T etranitromethane (C(NO 2 ) 4 ,T NM) constitutes such an example.I ti so ne of only six experimentally established pernitro carbon compounds,t he derivatives of methane [C(NO 2 ) 4 ], ethane [C 2 (NO 2 ) 6 ], [1] ethene [C 2 -(NO 2 ) 4 ], [2] benzene [C 6 (NO 2 ) 6 ], biphenyl [C 12 (NO 2 ) 10 ], [3] and cubane [C 8 (NO 2 ) 8 ]. [4] TNM is well-known (m.p.1 3 8 8C, b.p.…”
mentioning
confidence: 99%